Turnover Intention Among Generation Z: Emerging Challenges in Human Resource Management - Setiawan, Abdi; Wakhyuni , Emi (Universitas Dehasen Bengkulu, 2025)
This study examines the factors influencing turnover intention among Generation Z employees, a cohort known for its distinctive work values, rapid career mobility, and high expectations for workplace flexibility. Using a quantitative approach, data were collected from 180 respondents across various industries to analyze the effects of job satisfaction, organizational culture, meaningful work, and work–life balance on turnover intention. Descriptive analysis shows that Generation Z exhibits a relatively high level of turnover intention, reflecting their strong desire for personal growth, meaningful career experiences, and supportive work environments. Validity and reliability tests confirm that all measurement instruments are robust and reliable. Correlation analysis reveals that all independent variables are negatively and significantly related to turnover intention. Multiple regression results indicate that work–life balance is the most dominant factor, followed by job satisfaction, organizational culture, and meaningful work. These findings highlight the need for organizations to adapt their human resource management strategies to better meet the expectations of Generation Z, particularly by fostering flexible working arrangements, enhancing job satisfaction, and cultivating an inclusive and innovative organizational culture. The study contributes to the growing literature on generational workforce dynamics and provides practical insights for improving talent retention in modern workplaces.